2014
DOI: 10.1007/978-1-4939-1396-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Regulation of Galectin-3 Expression in Cancer

Abstract: Galectin-3, a member of a β-galactoside-binding protein family, is involved in normal growth development as well as cancer progression and metastasis, but the detailed mechanisms of its functions or its transcriptional regulations are not well understood. Besides, several regulatory elements such as GC box, CRE motif, AP-1 site, and NF-κB sites, the promoter of galectin-3 gene (LGALS3) contains several CpG islands that can be methylated during tumorigenesis of prostate leading to the gene silencing. Here we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This is not consistent with the results obtained by Lambropoulou et al where high expression of galectin 3 was independently associated with the infiltration depth and the histological grade of the tumor [ 25 ]. Both proliferative and apoptotic effects of galectin 3 are well illustrated by Hafiz et al who demonstrated that galectin 3 as expressed on the surface of cells is involved in homotypic cell adhesion via binding to soluble complementary glycoconjugates [ 26 , 27 ]. Interactions between metastatic neoplastic cells with vascular endothelium are critical in the early stages of tumor metastasis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not consistent with the results obtained by Lambropoulou et al where high expression of galectin 3 was independently associated with the infiltration depth and the histological grade of the tumor [ 25 ]. Both proliferative and apoptotic effects of galectin 3 are well illustrated by Hafiz et al who demonstrated that galectin 3 as expressed on the surface of cells is involved in homotypic cell adhesion via binding to soluble complementary glycoconjugates [ 26 , 27 ]. Interactions between metastatic neoplastic cells with vascular endothelium are critical in the early stages of tumor metastasis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 6 Galectin-3 has several functions because it is expressed in different locations and can attach to a variety of ligands. 3 , 4 , 7 9 It also takes part in the transformation process and carcinogenesis. Several studies have shown that galectin-3 plays significant roles in a collection of neoplasm-associated biological activities including apoptosis, differentiation, adhesion, proliferation, migration, angiogenesis, invasion, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that galectin-3 plays significant roles in a collection of neoplasm-associated biological activities including apoptosis, differentiation, adhesion, proliferation, migration, angiogenesis, invasion, and metastasis. 5 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin-12 was shown to be silenced by DNA methylation in colorectal cancer (CRC) cell lines and primary samples (Xue et al, 2016;Katzenmaier et al, 2017). Moreover, previous studies showed that LGALS3 promoter CpG islands were heavily methylated in the early stages of prostate adenocarcinoma (Ahmed and Bandyopadhyaya, 2015). Interestingly, another study reported that the average methylation degree of five CpG sites in the LGALS3 gene regulatory region was significantly decreased in thyroid cancer tissues (Keller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%